Formation of diluted nitride InAs1–хNх core-shell nanowires on silicon - Kaveev Andrey; Fedorov Vladimir; Miniv Dmitriy (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
Epitaxial arrays of the InAs1–хNх core-shell nanowires have been synthesized on Si (111) for the first time. The growth of the nanowires with a wurtzite-type crystal structure was demonstrated by a self-induced mechanism using the molecular beam epitaxy with plasma-assisted nitrogen activation. Using the transmission electron microscopy and X-ray diffraction analysis, a volume decrease in the wurtzite crystal unit cell with increasing nitrogen content was revealed.